Using the life course paradigm to study financial well-being in late life - Pattharanitcha Prakitsuwan (2022)
Purpose: This study aims to show how the increasingly popular life course paradigm (LCP) can be employed as an alternative to the successful aging perspective (SAP) as an overarching conceptual research framework to study elderly consumers' financial well-being. Design/methodology/approach: A questionnaire was administered to a convenience sample of 804 Thai consumers over the age of 45 selected via the snowball method. Findings: Significant results were found for hypotheses derived from the LCP for older consumers' financial well-being, suggesting critical roles of early life experiences, developmental factors, adaptation mechanisms and contextual factors. Originality/value: This paper shows how efforts to study consumers over the course of their lives can be improved by utilizing the principles and theoretical perspectives of the LCP and offers research directions for studying not only older consumer well-being but also numerous consumer behavior issues at any stage of life in an innovative way.